Case Report: Combining Molar Interradicular Osteotomy With Immediate Implant Placement: A Three-Year Case-Series Study - Alagl, Adel S.; Madi, Marwa (Frontiers in Materials, 2022)
Background: Immediate implant placement in the area of multirooted molars includes many anatomical challenges, particularly with osteotomy preparation in the interradicular bone. Methods: In this article, we are reporting ten cases in which implant beds were prepared before root extraction. After coronectomy, pre-extractive interradicular implant bed preparations were performed through the retained root complexes. A dimple in the roof of the furcation was created using a no. 8 round surgical bur. The osteotomies were then completed through the tooth’s initially retained root complex in the regular sequence of drilling. Before implant placement, the remaining root segments were removed. The retained root parts guided the osteotomy drills and allowed for precise positioning and angulation of the implant bed preparation with respect to the emergence profile of the tooth. Results: Data from a 3-year follow-up of the crestal bone showed good bone levels in relation to the implant platform. Conclusion: The technique described permitted accurate implant placement in the prepared osteotomy, thus enabling immediate implant positioning in multirooted extraction sites.